Genetic Ranking of Potato Varieties is Different in Scandinavian and Mediterranean Environments - Muhammad Farhan Yousaf; Hélène Romé; Merethe Bagge; Mathias Timmermann; Just Jensen; Thinh Tuan Chu (American Journal of Potato Research, 2026)
Understanding genotype-by-environment interaction (G×E) is essential for breeding potato cultivars adapted to different regions. We analyzed ~ 13,000 tetraploid breeding lines evaluated over 17 years in Denmark (DK), Spain (ES), and Morocco (MO), representing Scandinavian and Mediterranean mega-environments. A pedigree-based mixed model was fitted for yield, tuber size, and resistance towards scab. Significant G×E was detected for yield and scab, evidenced by lack of unit genetic correlations between environments, heterogeneous genetic variances, and differing heritabilities. Additive genetic correlations for yield were 0.54 (DK–ES), 0.64 (DK–MO), and 0.78 (ES–MO); scab correlation between DK and ES&MO was 0.6. Yield genetic variance in ES was more than twice compared with DK and MO, whereas scab variance was higher in DK. Tuber size showed weaker G×E (r a = 0.82). Within mega-environments, genotype × environment components explained 16.8–26.9% of yield variance. Results indicate substantial re-ranking of breeding values; therefore, environment-specific prediction is recommended.